Our experience in laboratory diagnosis of rotaviruses - Dvořáková Heroldová, Monika; Moutelíková, Romana; Holá, Veronika; Dvořáčková, Milada; Prodělalová, Jana (Klinicka mikrobiologie a infekcni lekarstvi, 2019)
OBJECTIVE: Group A rotavirus (RVA) is one of leading causes of gastroenteritis in children under five years of age and is also an important nosocomial pathogen. In Europe, the most prevalent genotypes of RVA are G1P[8], G2P[4], G3P[8], G4P[8], G9P[8] and G12P[8]. Severe dehydration is the most important complication of RVA gastroenteritis. Each year, rotavirus infection is responsible for 3,000 to 5,000 hospitalizations of children in the Czech Republic. The aim of this study was to detect rotaviruses in patients with suspected acute viral gastroenteritis. METHODS: A total of 1 566 stool samples were obtained from patients with acute gastroenteritis from March 2016 to December 2018. All samples were tested by the enzyme immunoassay, rapid immunochromatographic test and quantitative reverse transcription PCR assay to detect RVA. All RVA positive samples were G- and P-typed by Sanger sequencing. RESULTS AND CONCLUSION: RVA was detected in 13.7 % of the samples (214/1566). The incidence of RVA was 58.9 % (126/214) in males and 41.1 % (88/214) in females. The percentages of positivity ranged from 1 % to 33 % in different age groups. The highest proportion of positive patients was in the age group 4-5 years, 32.6 % (30/92). There was a significant difference in the incidence of rotaviruses between different age groups (p = 0.3946). The prevalent RVA genotypes were G1P[8], G9P[8], G3P[8], G2P[4] and G8P[8]. The detection of the G8P[8] genotype was unusual. The obtained results show that despite the possibility of vaccination, the incidence of RVA infection remains high in the Czech Republic.
Keywords: Rotavirus; Immunoassay; klinické laboratorní techniky; Genotype; Female; Infant; Clinical Laboratory Techniques; dítě; předškolní dítě; ženské pohlaví; RNA, Viral; lidé; genotyp; polymerázová řetězová reakce s reverzní transkripcí; RNA virová; imunoenzymatické techniky; Incidence; Male; Reverse Transcriptase Polymerase Chain Reaction; incidence; imunoanalýza; kojenec; Czech Republic; Rotavirus Infections; Child, Preschool; Immunoenzyme Techniques; Česká republika; Child; mužské pohlaví; rotavirové infekce; Humans